Mental Stress–Induced Myocardial Ischemia: When the Mind Controls the Fate of the Heart - Bravo, Paco E; Cappola, Thomas P (JAMA : the journal of the American Medical Association, 2021)
Coronary heart disease (CHD) is the leading cause of mortality globally, and patients who have chronic forms of CHD experience substantial morbidity, including high rates of recurrent cardiac events and eventual onset of heart failure.1,2 Further research to identify vulnerable populations, improve risk stratification, and understand nontraditional risk factors is essential to reduce the public health burden of CHD.